The IndiQoS Message Broker: an Instantiation Using RSVP - Araújo, Filipe (2009)
This paper describes the first proof-of-concept implementation of the IndiQoS architecture: a system that intends to support the seamless integration of QoS provision in publish-subscribe systems. A unique feature of the IndiQoS architecture, is that applications are structured following the publish-subscribe paradigm and express QoS parameters with constructs similar to those used to handle other aspects of the data flow, such as the ones used to express interest in a particular subject or content. Although we aim to build a system that is able to manage different QoS mechanisms at the network and operating system level, the current paper focus on the use of RSVP and integrated services in the IndiQoS architecture. Two main aspects are studied: definition of QoS parameters for use by publish-subscribe applications and optimal assignment of data network resources for a given configuration of publishers and subscribers